Garment Factories of Uzbekistan in Soviet Period - Anvarovna, Gaybullayeva Yulduz (Research Parks Publishers, 2023)
In 1950-1991, several factories were established in the field of sewing. This was mainly due to the fact that the Soviet government emphasized the production of factory products during this period. On the other hand, each garment factory has its own history. Some of them were enterprises transferred from the war zones during the Second World War, while some of them were converted into sewing factories of the local handicraft production enterprises in the area. In addition, several new garment factories were opened.